Connecting Tibetan Plateau Snow Change With Arctic Sea‐Ice - Chao Zhang; Anmin Duan; XiaoJing Jia; Shizuo Liu (Geophysical Research Letters, 2025)
Abstract Documenting changes in the Arctic sea‐ice variability are essential for understanding the spring sea‐ice predictability barrier. While Tibetan Plateau snow cover (TPSC) has been linked to Arctic sea‐ice variability, the spatiotemporal stability of this relationship remains unclear. In this study, combing satellite observations and snow experiments, we identified a shift in connections between TPSC and Barents‐Kara Seas sea‐ice around 1990. Before 1990, a positive dipole TPSC pattern (eastern enhanced/western reduced snow cover) induces Arctic anticyclonic anomalies through a circumglobal wave train. These anomalies facilitate polar vortex splitting, enhancing moisture transport and solar radiation over the northern Kara Sea, which accelerates sea‐ice reduction. Conversely, post‐1990, a positive monopole TPSC pattern (positive snow anomalies on the entire Tibetan Plateau) strengthens the polar vortex, suppressing Barents Sea (BS) moisture and solar radiation, thereby promoting sea‐ice growth. This regime shifts underscore TPSC's capacity to modulate Arctic sea‐ice dynamics through polar vortex system.